A Lead‐Free All‐Inorganic Metal Halide with Near‐Unity Green Luminescence. Issue 5 (10th March 2020) - Zhang, Ruiling; Mao, Xin; Zheng, Daoyuan; Yang, Yang; Yang, Songqiu; Han, Keli
Abstract: As the increasing demand of lighting display technology, environmentally‐friendly, economic light‐emitting materials with high performance are required. Herein, a novel solution‐processed, highly emissive copper chloride compound β‐Cs3 Cu2 Cl5 is reported. The crystal structure determined by the Rietveld refinement of the powder X‐ray diffraction patterns shows that the corner‐sharing tetrahedral Cu–Cl chains are surrounded by Cs + cations, yielding a one‐dimensional structure at molecular level. The all‐inorganic compound shows excellent photostability, and is thermally stable up to 550 °C. Excitingly, it exhibits room‐temperature photoluminescence in the green region with near‐unity quantum yield. Currently, this appears to be the most efficient lead‐free all‐inorganic green‐light emitting metal halides reported. This work presents a new direction toward the design of high‐efficiency, economic, and environmentally‐friendly light‐emitting materials. Abstract : A nontoxic, thermally‐stable copper chlorine compound β‐Cs3 Cu2 Cl5 with near‐unity green luminescence efficiency is synthesized and characterized. The emission mechanism is revealed by combination of spectral techniques and first‐principles calculations. The highly efficient emitter can be obtained via facile solution processing, and this work presents a new direction toward the design of high‐efficiency, economic, and environmentally‐friendly light‐emitting materials.